Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1111/ene.15565
|View full text |Cite
|
Sign up to set email alerts
|

Role of autoantibody levels as biomarkers in the management of patients with myasthenia gravis: A systematic review and expert appraisal

Abstract: Background and purpose: Although myasthenia gravis (MG) is recognized as an immunoglobulin G autoantibody-mediated disease, the relationship between autoantibody levels and disease activity in MG is unclear. We sought to evaluate this landscape through systematically assessing the evidence, testing the impact of predefined variables on any relationship, and augmenting with expert opinion. Methods:In October 2020, a forum of leading clinicians and researchers in neurology from across Europe (Expert Forum for Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
0
7
0
2
Order By: Relevance
“…
We appreciate the comments from Li et al [1] on aspects of our article entitled "Role of Autoantibody Levels as Biomarkers in the Management of Patients With Myasthenia Gravis: A Systematic Review and Expert Appraisal." [2] We agree that titin autoantibody Data sharing not applicable to this article as no datasets were generated or analysed during the current study.
…”
mentioning
confidence: 85%
“…
We appreciate the comments from Li et al [1] on aspects of our article entitled "Role of Autoantibody Levels as Biomarkers in the Management of Patients With Myasthenia Gravis: A Systematic Review and Expert Appraisal." [2] We agree that titin autoantibody Data sharing not applicable to this article as no datasets were generated or analysed during the current study.
…”
mentioning
confidence: 85%
“…The activity of MG is difficult to define. Although a correlation was found between AChR antibody level and severity at group level in Meisel et al's report [1], inconsistent trends of AChR antibody level and severity were found in a certain proportion of individual patients, either at a time-point or over an interval [4].…”
mentioning
confidence: 87%
“…We appreciate Meisel et al [1] for exploring the correlation between antibody level and activity of myasthenia gravis (MG). However, some concerns are raised here.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, clinical disease characteristics and laboratory data (eg, autoantibody status, thymus histology) should guide management alongside the clinical outcomes. 86 Recently, microRNAs (miRNAs), non-coding RNA secreted by many cell types, emerged as relevant molecules in the pathogenesis of several human disorders, including neuromuscular disorders such as myasthenia. Of these miRNAs, miR-150-5p, miR-21-5p, and miR-30e-5p levels have been reported to correlate with the clinical response after immunosuppression and to predict the generalization of OMG in some studies.…”
Section: Risk Of Generalization Of Omgmentioning
confidence: 99%